“Desarrollo de modelos de simulación de comunicaciones analógicas y Digitales con fines Pedagógicos” - Aguirre Alvarez, Cristian Raúl (2016)
The Electronics and Telecommunications School of the Universidad Nacional de Chimborazo has a hardware and software of the National Instruments company which by the lack of specific knowledge is not used in its sum, since its management and use is only limited to certain practices. This project aims at the development of models for the simulation of analog and digital communications for educational purposes. They were developed to gather the necessary information to determine the mathematical models of the most important modulations in the area of telecommunications. According to the academic programs of the subjects of Analog Communications and Digital Communications each of the sustainable practices were determined, with the assistance of the manual of laboratory practices, using as a simulation tool LabVIEW software ownership of the National Instruments Company. The result was that laboratory practices carried out with students from fifth and sixth semester, they complemented the theoretical knowledge acquired in class and at the same time improving their learning in the area of electronic communications. This could be checked using the method of Chi-Square test with the data obtained from the surveys applied to the students of the subjects relating to the research topic, this test allowed us to reject the null hypothesis. The manual allows the highway practices in function of the modelling using the software, the particular simulations were created based on the general equations of each type of modulation. In a specific case to model various Digital Modulations was necessary to analyse, study and understand block diagrams that make reference to the process of obtaining a specific type of modulation.